Role of Different Exercise Modalities in the Management of Obstructive Sleep Apnea: A Narrative Review - Kukla, Monika; Bulicz, Anna; Kmiecik, Izabela; Kowalczyk, Olga; Zdunek, Marta; Stodulski, Maciej; Kasprzycka, Izabela; Dziarnowska, Joanna; Kozłowski, Sebastian; Justyna Fiks (Quality in Sport, 2026)
Background. Obstructive sleep apnea (OSA) is a common breathing disorder associated with excessive daytime sleepiness, impaired quality of life, and increased cardiovascular and metabolic risk. Although continuous positive airway pressure (CPAP) remains the first-line treatment, long-term adherence is often suboptimal, prompting interest in adjunctive therapies. Aim. To evaluate the effects of different exercise modalities on outcomes in OSA and assess their role as adjunctive therapies. Material and methods. A narrative review of the literature was conducted to identify studies evaluating aerobic exercise, resistance training, respiratory muscle training, and oropharyngeal exercises in adults with OSA. Outcomes included AHI, ESS, BMI, and CPAP adherence. Results. Exercise-based interventions may improve both objective and subjective outcomes in patients with OSA. Aerobic exercise showed the most consistent reductions in AHI and improvements in daytime sleepiness, sleep quality, and cardiometabolic health. Combined aerobic and resistance training appeared more effective than resistance or aerobic training alone, particularly in reducing OSA severity and improving anthropometric outcomes. Respiratory muscle training showed promising effects on sleep-related symptoms, although its impact on AHI remains inconsistent. Oropharyngeal exercises showed the most consistent AHI reductions and may improve CPAP adherence by enhancing upper airway muscle function. Several beneficial effects were observed independently of significant weight loss. Conclusions. Different exercise modalities appear to target distinct pathophysiological mechanisms of OSA and provide complementary therapeutic benefits. Exercise should be considered a valuable adjunct to standard OSA treatment, while further high-quality studies are needed to establish optimal exercise protocols and phenotype-based therapeutic strategies.